1979
DOI: 10.1902/jop.1979.50.6.301
|View full text |Cite
|
Sign up to set email alerts
|

Sulcular Exudate Flow in Gingival Inflammation

Abstract: Sulcular exudate flow measurements were obtained from 45 subjects and compared to the clinical as well as histologic degrees of inflammation. The results of this investigation demonstrated no statistically significant difference between exudate flow and the clinical degree of inflammation while demonstrating a statistically significant difference between exudate flow and the clinical assessment of inflammation. It was proposed that current clinical indices do not accurately reflect the microscopic degree of gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 9 publications
4
29
0
Order By: Relevance
“…Uttio 16) reported that in periodontitis, increased in GCF volume was associated with increased in probing pocket depth and deeper pockets were associated with higher GCF volume. Finding in the present study supports the suggestion that GCF volume increases with gingival inflammation and periodontitis 14,18,38,39) . In the present study, when GCF volume was compared at healthy gingival sites in all 3 groups, there was significant increase in GCF volume in both gingivitis and periodontitis group compared to healthy gingival group.…”
Section: Discussionsupporting
confidence: 92%
“…Uttio 16) reported that in periodontitis, increased in GCF volume was associated with increased in probing pocket depth and deeper pockets were associated with higher GCF volume. Finding in the present study supports the suggestion that GCF volume increases with gingival inflammation and periodontitis 14,18,38,39) . In the present study, when GCF volume was compared at healthy gingival sites in all 3 groups, there was significant increase in GCF volume in both gingivitis and periodontitis group compared to healthy gingival group.…”
Section: Discussionsupporting
confidence: 92%
“…[44][45][46] Moreover, inflamed sites in patients with periodontitis (G-AgP and CP) and gingivitis had higher GCF volumes compared to healthy ones, which reflects the severity of gingival inflammation in diseased groups. 44,46,47 Moreover, GCF volume, which is the indicative of the degree of gingivitis, 46 was higher in gingivitis group compared to periodontitis groups.…”
Section: Discussionmentioning
confidence: 90%
“…33,53 Studies showed low production of these novel molecules by inflammatory cells. 15,16,24,47 IL-33 is inactivated by apoptotic caspases, which results in dampening of proinflammatory properties of IL-33. 27,29,54 Moreover, IL-33 decreases inflammation opposite of the other pro-inflammatory molecules and act more as an immunoregulatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of periodontal disease is site-specific [1], and increased numbers of lymphocytes, neutrophils and macrophages are recognized in early lesions [2][3][4]. Gingival crevicular fluid (GCF) flow also increases during gingival inflammation [5,6].…”
Section: Introductionmentioning
confidence: 99%